2020
DOI: 10.1002/ajb2.1416
|View full text |Cite
|
Sign up to set email alerts
|

Fossil evidence for a Cretaceous rise of the mahogany family

Abstract: Premise The mahogany family (Meliaceae) is an angiosperm lineage comprising many species that are important elements in tropical ecosystems, and is often used as a study system to understand the evolution of tropical rainforests. While divergence time studies have estimated a Cretaceous origin for the family, no unequivocal fossils of that age have been described. Here, the first Cretaceous evidence for Meliaceae is reported, based on an exceptionally well‐preserved fruit from the Upper Cretaceous (79–72 Ma, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Meliaceae comprise c. 740 validly described, accepted tree and shrublet species, taxonomically arranged in 58 genera (Muellner‐Riehl & Rojas‐Andrés, 2021). The estimated crown age of Meliaceae dates back to the Late Cretaceous, based on phylogenetic approaches (Koenen et al, 2015: 80.4 million years ago, Ma, 95% probability interval 69.1–91.6 Ma; Muellner‐Riehl et al, 2016: 79.6 Ma, 95% probability interval 69.66–89.77 Ma; Joyce et al, 2023: 86.3 Ma, 95% probability interval 72.27–97.74 Ma or 109 Ma, 95% probability interval 89.1–131.5 Ma) which is also in line with the oldest known fossil in the family ( Manchestercarpa vancouverensis Atkinson (72–79 Ma); Atkinson, 2020). Best represented in terms of both abundance and species numbers in the region within Meliaceae is Dysoxylum s.l., the target group of our study, composed of Dysoxylum s.s. (28 species), Didymocheton (43 species), Epicharis (seven species), Goniocheton (four species), Prasoxylon (seven species) and Pseudocarapa (six species) (Holzmeyer et al, 2021).…”
Section: Introductionsupporting
confidence: 56%
“…Meliaceae comprise c. 740 validly described, accepted tree and shrublet species, taxonomically arranged in 58 genera (Muellner‐Riehl & Rojas‐Andrés, 2021). The estimated crown age of Meliaceae dates back to the Late Cretaceous, based on phylogenetic approaches (Koenen et al, 2015: 80.4 million years ago, Ma, 95% probability interval 69.1–91.6 Ma; Muellner‐Riehl et al, 2016: 79.6 Ma, 95% probability interval 69.66–89.77 Ma; Joyce et al, 2023: 86.3 Ma, 95% probability interval 72.27–97.74 Ma or 109 Ma, 95% probability interval 89.1–131.5 Ma) which is also in line with the oldest known fossil in the family ( Manchestercarpa vancouverensis Atkinson (72–79 Ma); Atkinson, 2020). Best represented in terms of both abundance and species numbers in the region within Meliaceae is Dysoxylum s.l., the target group of our study, composed of Dysoxylum s.s. (28 species), Didymocheton (43 species), Epicharis (seven species), Goniocheton (four species), Prasoxylon (seven species) and Pseudocarapa (six species) (Holzmeyer et al, 2021).…”
Section: Introductionsupporting
confidence: 56%
“…18; see also Devecchi et al, 2018). A recent finding of a fossil of a permineralized fruit assignable to a Meliaceae from the Upper Cretaceous (79‐72 Ma, Campanian) of western North America is consistent with this hypothesis: The fruit consists of a fleshy mesocarp and a thick woody endocarp, hence a drupe, and is the first evidence of Meliaceae from the Cretaceous and is among the earliest representatives of the order Sapindales (Atkinson, 2020). As we previously discussed, a septifragal capsule appears as a synapomorphy of the Cedreloideae clade (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…The work by Muellner et al (2006) thus supported the idea that the entry of megathermal (frost-intolerant) angiosperms into southern continents from Oligocene to Pliocene must be considered as an important means of establishing modern pantropical distribution patterns. It is worth to note here that indeed the currently oldest known fossil of Meliaceae is an exceptionally well-preserved fruit from the Upper Cretaceous (79-72 Ma, Campanian) of North America (Atkinson 2020). A family-scale macroevolutionary study by Koenen et al (2015), focusing on temporal dynamics of evolution of rainforest clades within Meliaceae, suggested that these rainforest clades diversified from the Late Oligocene or Early Miocene onwards, and that most species-level diversity of Meliaceae in rainforests was rather recent.…”
Section: Biogeographic Studies On Modern Meliaceaementioning
confidence: 88%